Decline and Response? Lifecycle Change and Housing Estates in Birmingham, England. - Murie, Alan (Springer Open, 2018)
This chapter discusses mass public housing estates in England and uses Birmingham to illustrate how estates have changed. In British cities, large housing estates built between the 1950s and 1970s are particularly associated with flats and tower blocks. They formed an important part of public housing, but failures in design, construction, management and maintenance meant that they often also damaged its status and reputation. Estates have changed over time and this Chapter, highlights internal and external influences and demolition, privatisation and regeneration. These influences have been layered on each other and interacted to generate different outcomes in different places. Some estates and properties from this era have proved popular and successful, but in other cases questions have arisen about their construction, suitability for disadvantaged communities and continuing role. The failures of some estates and of their regeneration are likely to continue to generate demands for demolition and substantial funding for their redesign.
Keywords: Wohnungswesen; Wohnsiedlung; Privatisierung; Fallbeispiel; Großwohnsiedlung